Growth analysis of the lower layer trees in forest stands under conversion in the Starohorské vrchy Mts.: A case study - Stanislav Kucbel; Jaroslav Vencurik (Journal of Forest Science, 2022)
The case study analyses the structure and dynamics of the diameter growth on the example of two fir-spruce forest stands under conversion to a selection forest. In a series of 51 circular research plots (size 500 m2), the biometric characteristics (tree species, diameter at breast height, height) of all the stems with a diameter above 8 cm were registered. From the selected stems, we collected 51 cross-sections and 178 tree cores in total and performed age and growth analyses. In addition, for the lower layer trees, we assessed the competition by the neighbouring stand quantified by the competition index. The results confirmed the differences in the age structure, despite the similar diameter distributions in the investigated stands, as well as the differences in the growth dynamics of the spruce and fir in the lower tree layer. Nevertheless, the competition of the neighbouring stand was not proven as a significant factor for the diameter growth of the lower layer trees.